1993
DOI: 10.1159/000187560
|View full text |Cite
|
Sign up to set email alerts
|

Value of Urinary Endothelin-1 in Patients with Primary Vesicoureteral Reflux

Abstract: By using a radioimmunoassay specific for endothelin-1 (ET-1), we measured urinary excretion of ET-1-like immunoreactivity (LI) in 63 spot urine samples of 48 patients with primary vesicoureteral reflux (VUR). And also, urinary excretion of N-acetyl-β-D-glucosaminidase (NAG), β2-microglobulin (β2-MG), microalbumin (Alb) and creatinine (Cr) were measured. There was no significant correlation in any of the pairs ET-1 and NAG, ET-1 and β2-MG, and ET-1 and Alb. Comparing the grade o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…It was speculated that these elevated ET1 levels are the result of circulating plasma factors (eg, LPS and ST) that stimulate its production by endothelial and/or renal epithelial cells. However, as elevated urinary ET excretion has been observed in other glomerular dis eases 109 and patients with renal tubular injury, 110 its spe cific role in HUS awaits further evaluation.…”
Section: Pathogenesismentioning
confidence: 98%
“…It was speculated that these elevated ET1 levels are the result of circulating plasma factors (eg, LPS and ST) that stimulate its production by endothelial and/or renal epithelial cells. However, as elevated urinary ET excretion has been observed in other glomerular dis eases 109 and patients with renal tubular injury, 110 its spe cific role in HUS awaits further evaluation.…”
Section: Pathogenesismentioning
confidence: 98%
“…In patients with vesicoureteral reflux (VUR) high levels of urinary β2-microglobulin, N-acetyl-β-D-glucosaminidase, and microalbumin have been reported [78]. Komeyama et al [79] found no correlation between any of these factors and the renal ET-1/creatinine ratio in spot urine samples, both in adults and in children, in agreement with our results [63]; however ET-1/creatinine increased in proportion to the grade of reflux, except for grade 5 reflux where it was decreased. Thus ET-1 may be an indicator of renal tubular injury in patients with primary VUR.…”
Section: Et Excretion In Tubular Disturbances (Diabetic Ketoacidosismentioning
confidence: 99%
“…In reflux group, there was no correlation between endothelin levels and age and gender. Two research works stated that urinary endothelin-1 excretion in patients with primary VUR was significantly higher than normal, and it increased in proportion to the grade of reflux (4,5). However, based on dimercaptosuccinic acid (DMSA) uptake, they did not find any relationship between endothelin level and renal parenchymal and function damage (4,5).…”
Section: Discussionmentioning
confidence: 99%